State fragility and international development cooperation - Balázs Szent-Iványi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
Over the past few years addressing state fragility in the third world has become an important priority in international development cooperation. However, it seems that the international donor community has so far not been able to develop adequate instruments for dealing with the problems posed by state failure. We see two reasons for this: (i) there is growing recognition within the donor community that the lack of absorptive capacity, or bad economic policies in the partner country can actually make aid counterproductive, even harmful; and (ii) it is very difficult to manage effective development cooperation with weak governments. Channelling aid through NGOs, or giving limited aid in the form of capacity-building is clearly not sufficient to solve the problems fragile states face. In order to minimize distortions caused by aid, the literature advocates a policy-based selective approach, i.e., limiting aid funds to recipients with `good policies'. However, failed states (and many weak states for that matter) do not have the capability to formulate good economic policies, and some countries face serious challenges in meeting the criteria of good policies posed by the World Bank/IDA or the US in its Millennium Challenge Account. An important reason for this is that reforms within recipient countries aimed at forming good policies (especially liberalizing international trade, curbing inflation and cutting the budget deficit) create winners and losers, and the losers in fragile states can be strong enough to block policy changes or even cause conflict. We conclude that in order to better help weak states, the criteria for good policies must also include criteria for forming policies that compensate losers. Donors must help recipients in formulating such policies. To further ensure that losers of policy reforms do not block change, donors must pay greater attention to conflict prevention and social mediation in weak states, and to conflict management and peacebuilding in the case of failed states.
Keywords: O19; F59; F42; O23; O57; 330; development cooperation; aid; failed states; state failure; absorptive capacity; Dutch disease; selectivity; good policies; Millennium Challenge Account; Staatsversagen; Entwicklungskooperation